Stress distribution in cortical bone around the basal implant – A finite element analysis - Anip Kumar Roy; Nivedita Dixit; Prashant Punde; Koshika Tondon Sinha; Mohammad Jalaluddin; Ashish Kumar (Journal of Pharmacy and Bioallied Sciences, 2021)
Aim: The aim of the study was to develop a model that represents a basal implant with stress distribution in the cortical bone on application of loads emulating masticatory forces. Materials and Methods: In this study, the stress distribution in the bone and the implant is evaluated by applying various loads that emulate the masticatory forces. The geometric models of cortical bone representing the premolar area and a basal implant model of the following specifications, longitudinal oval threaded pin (1.95 mm × 2.1/2.3 mm ø), height of the implant head (7.2 mm), and width of the implant head (3.5 mm) (BOI BS, IDHEDENTAL), were generated with Ansys software, and both the implant model and the bone model are superimposed to mimic the bone implant system as a unit. Results: Overall comparison of stress distribution on both implant shaft and implant neck showed that maximum stresses are located at implant neck irrespective of forces applied and minimum stresses are located at implant shaft. On overall comparison of stresses seen within the bone and the implant, it was observed that the maximum stresses were seen in the implant neck followed by the implant shaft followed by the bone interface. Conclusion: The present study concluded that the stress transmission is greatest during application of oblique load (70 N) followed by horizontal load (10 N) and the least by vertical load (35 N).